COMPOSITION OF THE ESSENTIAL OILS OF LAVANDULA STOECHAS L. SUBSP. STOECHAS (BOISS.) - Alan, S.; Altintas, A.; Demirci, B.; Koca, F.; Baser, K. H. C. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
The genus Lavandula (Lamiaceae) represented with 2 species and 3 taxa in the Flora of Turkey (1). L. stoechas is used as analgezic, antiseptic, wound-healing, sedative, expectorant, treatment of eczama wounds and as cardiotonic (2). Aerial parts of Lavandula stoechas L. subsp. stoechas (Boiss.) were subjected to hydrodistillation for 3 h using a Clevenger-type apparatus to yield 1.16% oil. The oil was analysed by gas chromatography-mass spectrometry (GC-MS). Forty five compounds representing 97.4% of the essential oil were characterized from Lavandula stoechas subsp. stoechas. Camphor (45.8%), ï¡-fenchone (31.8%), bornyl acetate (4.2%) and camphene (2.5%) were the main constituents in the oil of Lavandula stoechas subsp. stoechas. References: 1. Davis, P.H., Flora of Turkey and the East Aegean Islands, Vol.7, 76-77, University Press. Edinburgh (1982). 2. Baytop, T., TÃ¼rkiye’de Bitkiler ile Tedavi, Ä°st. Ãœniv. YayÄ±n No: 3255 Ecz. Fak. YayÄ±n No:40, Ä°stanbul (1984).